2010
DOI: 10.1007/s11666-010-9514-z
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Spraying Angle on Properties of HVOF Sprayed Hardmetal Coatings

Abstract: The spraying angle is one of the deposition parameters that influence the quality of thermally sprayed coatings. In theory, decreasing the spraying angle results in lower process deposition efficiency, whereas the porosity of coatings increases, becoming a cause of poorer microstructure and mechanical properties. In this study, the dependence of microstructure together with the basic mechanical properties and wear of WC-Co and Cr 3 C 2 -NiCr high-velocity oxyfuel (HVOF) sprayed coatings on the spraying angle w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Maximum DE is found at the spraying angle of 90 (Houdková et al, 2010). Maximum DE is found at the spraying angle of 90 (Houdková et al, 2010).…”
Section: Feedrates and Dementioning
confidence: 87%
See 1 more Smart Citation
“…Maximum DE is found at the spraying angle of 90 (Houdková et al, 2010). Maximum DE is found at the spraying angle of 90 (Houdková et al, 2010).…”
Section: Feedrates and Dementioning
confidence: 87%
“…The DE for gas-fueled spray guns is higher (50-70%) than for liquid-fueled guns (35-50%) (Davis, 2004). The DE for liquid-fueled processes for WC-based coatings is only slightly above 40% and for Cr 3 C 2 -NiCr, below 40% (Houdková et al, 2010;Schwetzke et al, 2006). The DE for liquid-fueled processes for WC-based coatings is only slightly above 40% and for Cr 3 C 2 -NiCr, below 40% (Houdková et al, 2010;Schwetzke et al, 2006).…”
Section: Feedrates and Dementioning
confidence: 99%
“…With a reduction of the spray angle, the tangential component of the in-flight particle velocity with respect to the substrate surface is increased, while the normal component is reduced. Also, a reduction of coating microhardness with lower spray angles has been reported in the literature (Strock et al, 2001;Candel, 2009;Houdková et al, 2010) and can be related to the higher coating porosity. The velocity tangential component promotes particles spreading over the substrate, giving rise to elongated splats.…”
Section: Introductionmentioning
confidence: 74%
“…Despite the reduced hardness and 3 compressive residual stress of off-angle sprayed coatings, Strock et al [4] firstly reported an unexpected wear resistance enhancement for off-angle HVOF sprayed WC-CoCr coatings in comparison with that of normal angle sprayed coatings during dry fretting wear test against NiAl-bronze alloy or AISI 4340 steel wear pair under a load of 1.8 MPa and a frequency of 300 Hz for 8 h or 16 h. The exceptional wear response was attributed to more uniformly distribution of phases across the coating surface at off-angle spraying, and the enhanced wear resistance of off-angle sprayed coatings also caused greater wear of the wear pairs. More recently, Houdkova et al [5] confirmed poorer wear behavior of off-angle HVOF sprayed hardmetal coatings evaluated by a dry sand/rubber wheel test under low-stress condition with a load of 22 N and a sliding distance of 1.436 m, where significant reduction in wear resistance was observed at less than 45° for WC-17Co coatings and less than 60° for Cr 3 C 2 -NiCr coatings, with a high wear rate of nearly doubled for WC-Co and over doubled for Cr 3 C 2 -NiCr as comparing the 30° sprayed coating to that of normal angle. Recalculating the reported data, the specific wear rate could be estimated to within a range of 10 -4 -10 -5 mm 3 /Nm.…”
Section: Introductionmentioning
confidence: 97%
“…Off-angle spraying is indispensable for thermal spray technologies in industrial practice to coat components of complicated shape [1][2][3]. It has been reported that off-angle thermal spray may lead to notable degradation of coatings features and characteristics, for surface features mainly including higher porosity (lower density) and cracking [1,5], and for surface characteristics including lower microhardness [1,4,5], lower fracture toughness [2,5] or less compressive residual stress [4,5], respectively. Among the different thermal spray technologies, high-velocity oxy-fuel (HVOF) spraying has advantage in the off-angle spraying capable of obtaining denser coatings over other techniques such as plasma spraying and wire arc spraying, as a result of the higher velocity of powders accelerated by the HVOF spray flame [1].…”
Section: Introductionmentioning
confidence: 99%